Struktur Kalimat Bahasa Melayu Riau Dialek Kampar - Sri Rahayu; Ermawati Sulaiman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This study examines the sentence structure of Riau Malay dialect of Kampar in Pulau Birandang Village, Kampa District, Kampar Regency. The problem raised in this study is, how is the structure of the single sentence contained in the Riau Malay dialect of Kampar in Pulau Birandang Village, Kampa District, Kampar Regency. The theory that the author uses in this study is the theory of Alwi, et al. (2003). The method that the author uses in this research is descriptive method. The results obtained in the single sentence structure of Riau Malay dialect of Kampar Island, Birandang Village, Kampa District, Kampar Regency, namely the sentences obtained were one hundred and fifteen single sentences consisting of twenty-four verbal predicated sentences of the type of transverse sentence, for example: we want to mancai palm jo, mancai means to search using the prefix me-, the sentence with the adjective predicate consists of forty-eight sentences, for example: inyo nak nio yaŋ goda means he wants something big, the word big indicates that the predicate is an adjective, the sentence with a nominal predicate consists of twenty example sentences: jomu clothes den ha means I want to dry clothes, the word clothes shows that the predicate is a noun, a sentence with a numeral predicate consists of twenty-three sentences, for example: den ko tuao badiadiok means I have seven siblings, the word ungu indicates that the predicate is a number.